The Intersectional Vulnerabilities of Migrant Women in Disaster Contexts: A Scoping Review of Mental Health Impacts During the COVID-19 Pandemic - Almuqati , Fahad Barrak Zamil; Alenazi, Mamdouh Ramadan; Alenazi, Hani Shaker; Alanazi, Abdullatif Thamer; Alotibi, Muhaya Ali Khalifh; Alharthi , Ysear Marzawg; Alyousif, Abdullah Khalil; Harissi , Haneen Jaber Yami; ALOTAIBI, MOHAMMED KHATIM DAKHILALLAH; Alyousef, Abdullah Saud; Al Zoman , Maged Abdulaziz; AL Otaibi , Begad Majeb; et al. (Journal of Ecohumanism, 2024)
Disasters disproportionately impact vulnerable populations, particularly migrant women, who face unique challenges exacerbated by their intersectional identities. The COVID-19 pandemic serves as a critical case study to explore these vulnerabilities, highlighting the heightened mental health risks and socio-economic adversities they encounter.This scoping review synthesized qualitative literature published between 2020 and 2023, focusing on the experiences of migrant women during the COVID-19 pandemic. A systematic search was conducted across PubMed, Scopus, and Web of Science, yielding fourteen studies that examined themes such as mental health, gender-based violence, and access to healthcare services.The analysis revealed that legal status and economic instability emerged as primary vulnerability factors, significantly impacting the mental health of migrant women. Key themes included the exacerbation of gender-based violence, barriers to accessing healthcare, and the detrimental effects of social isolation and lockdown measures. The intersectionality framework elucidated how these women’s unique challenges are compounded by societal inequalities.The findings underscore the necessity for tailored disaster response strategies that address the specific needs of migrant women. Inclusive policies must consider the social determinants of health to enhance resilience and improve mental health outcomes in disaster scenarios. The study identifies critical gaps in existing literature, advocating for further research into the intersectional vulnerabilities faced by migrant women during various disaster contexts.